Bacterial 1, 4-α-glucan branching enzymes: characteristics, preparation and commercial applications. (2nd April 2020) - Ban, Xiaofeng; Dhoble, Abhishek S.; Li, Caiming; Gu, Zhengbiao; Hong, Yan; Cheng, Li; Holler, Tod P.; Kaustubh, Bhalerao; Li, Zhaofeng
Abstract: The 1, 4-α-glucan branching enzymes (GBEs) are ubiquitously distributed in animals, microorganisms and plants. These enzymes modify the structure of both starch and glycogen; changing the frequency and position of branches by forming new α-1, 6-glucosidic linkages. In organisms, controlling the number and distribution of branches is an irreplaceable process that maintains the physiological state of starch and glycogen in the cell. The process is also the foundation for the industrial applications of GBEs. So far, a number of GBEs have been identified in eukaryotes and prokaryotes as researchers searched for GBEs with optimal properties. Among them, bacterial GBEs have received particular attention due to the convenience of heterologous expression and industrial applications of GBEs from bacteria than GBEs from other sources. The advantages of bacterial GBEs in potential applications stimulated the investigations of bacterial GBEs in terms of their structure and properties. However, full exploitation of GBEs in commercial applications is still in its infancy because of the disadvantages of currently available enzymes and of limited imagination with respect to future possibilities. Thus, in this review, we present an overview of the bacterial GBEs including their structure, biochemical properties and commercial applications in order to depict the whole picture of bacterial GBEs.